Pengembangan Website Karang Taruna Pemuda Pemudi Sejati Jambur Pulau Sebagai Media Promosi Produk Desa Berbasis Kecerdasan Buatan - Anita Sindar Ros Maryana Sinaga; Murni Marbun; Arjon Samuel Sitio (Abdimas Universal, 2022)
Building a website requires reliable skills that can be learned self-taught or through formal training institutions. The PKM implementation team plays a direct role in building the village through coaching and mentoring for the younger generation in Jambur Village, Perbaungan Island, who have been active in youth organizations. The rise in crime rates, the distribution of drugs, and the disinterest of village youths in continuing their education to higher education raise problems that must be addressed as soon as possible. PKM from STMIK Pelita Nusantara involves members of the Pemuda Pemudi Sejati youth group, the Jambur Pulau Village office and village craftsmen, later resulting in a partnership collaboration to produce an artificial intelligence-based village online shop website. Stages of PKM implementation, Stage-1: web programming training next Stage-2: website creation. Fundamental contributions to the target audience include developing a website for selling village products which is managed directly by members of the Youth Organization, so that it can suppress social problems in the younger generation. The members who are trained can develop the web so that later they are able to maintain the sustainability of the finished web site. The performance achievement of 98%-100% of service implementation is completed, resulting in youth youth websites, online promotion assistance to craftsmen partners.